Effects of arbuscular mycorrhizal fungus Glomus mosseae and phosphorus application on plant growth rate, essential oil content and composition of coriander (Coriander sativum L.) - Al-Amri, Salem M.; Elhindi, Khalid M; Sharaf El-Din, Ahmed F. (Progress in Nutrition, 2016)
This study evaluated the interactive effect of inoculation of Glomus mosseae, an arbuscular mycorrhizal fungus (AMF), and exogenous phosphorus (P) on growth, gas exchange, different nutrients, oil contents and composition in fruits of Coriander sativum L. Two contrasting concentrations of KH2PO4 (F0–without P, F1–100 mg kg−1) were applied. Soil P supply significantly promoted all growth parameters, P and N concentrations and most photosynthetic parameters of both mycorrhizal and non-mycorrhizal plants. It also partially inhibitions soil acid (ACP) and alkaline phosphatase (ALP). The mycorrhizal inoculation significantly increased growth responses, plant nutrients (P and N in shoot and root tissues), ACP, ALP, total soluble proteins in root tissues, fruit yield and essential oil contents compared to nonmycorrhizal plants. Those stimulations were related to the level of mycorrhizal colonization in the root tissues for each treatment. Mycorrhizal plants showed higher net photosynthetic rate, stomatal conductance and transpiration rate than nonmycorrhizal plants, especially in soil without added phosphorus. This suggests that an addition of soluble P to soil generally reduces the percentage of mycorrhizal colonization levels in coriander root tissues and consequently the mycorrhizal benefits. The results showed that coriander plants were highly dependent on AMF in non-fertilized soil when compared to fertilized soil with phosphorus. Essential oil content in plants inoculated was significantly higher than other treatments. Furthermore, oil composition improved with AMF inoculation. Linalool that enhance the essence quality, increased in inoculated plant compared to non-inoculated plants particularly in P deficient soil. Inoculation of arbuscular mycorrhizal fungi into coriander plants is a feasible alternative to increase growth, nutrition, essential oil production and reduce the use of P fertilizers required to obtain economic production of coriander under phosphorus-deficient soil condition.